Roma und Travellers Identitäten im Wandel - Gauß, Karl-Markus (innsbruck university press, 2015)
"""... in recent years, the scholarly preoccupation with so many aspects of the history, culture, language of the Roma has reached a level that was hardly imaginable two or three decades ago. ... the academic ivory tower has never existed as far as the Roma studies are concerned, because whoever researches Roma also does it to be able in his own way to portray the fatal and dangerous image that the public has long made of the Roma. to correct and disseminate knowledge that affects society. "" (Karl-Markus Gauss, preface The editors provide a broad overview of the social position of Roma, Yeniche and Travelers in Austria and in some other European countries. Living conditions and life contexts, languages ​​and cultural productions are just as much a topic as committed rebellion and organized visualization of these minorities (""minorities"" in the words of Ceija Stojka). Well-known scientists from various disciplines and activists have networked for this purpose, participated in workshops, lectures and conferences at the University of Innsbruck and make their decades of experience and research results available for this anthology."